FOOD, MODERNITY AND IDENTITY: ROOTED COSMOPOLITANISM IN ADICHIE’S AMERICANAH - Syarif Hidayat (English Department of Faculty of Tarbiyah and Teacher Training, 2021)
In globalization era, there are many producers of global foods that have localized their products in order to get more costumers. Indeed, there are some people who cannot be separated with their locality, although they are part of global citizen. This paper discusses the tug-of-war between cosmopolitanism and localism within the persona of Ifemelu, the main character in Americanah, specifically in what food she eats and how the food is eaten and its influence on her identity. Americanah is a novel that tells the story of a Nigerian immigrant living in the United States who decided to return to Nigeria. The study focuses on the characters and characterization of the figures in the novel and it aims to show how a rooted cosmopolitan identity was formed in Ifemelu. The study is a qualitative research using the rooted cosmopolitanism theory proposed by Kwame Anthony Appiah. The research shows that Ifemelu's rooted cosmopolitan identity was seen through the negotiation between her cosmopolitan identity and her local (Nigerian) identity. The discourse on rooted cosmopolitanism built by the text reveals its partiality toward Nigerian local culture, specifically the Nigerian foods.